Автоматизація бізнес-процесів в онлайн-оптиці: створення веб-системи замовлень та консультацій - Скирда, Д. А.; Імангулова, З. А. (ХНУРЕ, 2025)
This paper focuses on the development of an e-commerce information system for an optical store that improves the process of choosing and buying glasses. The system allows users to place a complete order online, from choosing a frame and selecting the appropriate lens characteristics to making a payment and organizing delivery to the specified address. AddІТionally, users can make an appointment wІТh an ophthalmologist to have their vision checked. The administrative module allows store employees to effectively manage orders. The implementation of the information system reduces paperwork, increases the speed of customer service, and improves the efficiency of the store.
Keywords: онлайн-оптика; веб-система замовлень; веб-система консультацій